GENRE ANALYSIS OF RESEARCH ABSTRACTS IN CENTRAL MINDANAO UNIVERSITY - Rene Marquez Bonifacio (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Research abstract provides a summary of a completed research article. This study aims to classify the pattern of the rhetorical moves, identify the obligatory and optional moves, and determine the linguistic features in the research abstracts of Central Mindanao University (CMU) undergraduate students. The study used content analysis and stratified random sampling. The corpora were the research abstracts written by the CMU undergraduate students in the Academic Year (AY) 2011-2015 using Genre-based Approach and Hyland’s Framework for Abstract Analysis (2000). The study reveals that the M2-M3-M4-M5 (purpose-method-product-conclusion) pattern obtained the highest number of occurrences with 159 or 50.96%. Purpose (M2), method (M3), and product (M4) are considered as the obligatory moves because these moves appeared in all of the samples. Various linguistic features are also found. The variations of the rhetorical move patterns, diverse optional moves, and distinctive linguistic features imply that the CMU undergraduate students are unaware of the genre of writing research abstracts.